Biography and History: The Historiography of Lee Kuan Yew. Issue 3 (3rd July 2019) - Ang, Cheng Guan
ABSTRACT: This article revisits the question of whether contemporary biography can be considered as history through a close examination of the political biographies (and autobiography) of Singapore's Prime Minister Lee Kuan Yew and the historiography of Singapore. According to the late British historian Benjamin Pimlott, widely respected for his contribution to the genre of political biography, it defies an easy answer. The answer remains complex and there is still no clear consensus. As Robert Jervis noted, however, "memoirs are as essential as they are misleading" (Jervis, 2013). For all its strengths and limitations, biography "is indispensable to understanding of motive and intention" and "the motives of individuals have some part to play in explaining historical events" (Pimlott, 1999). Through the historiography of Lee, this article also attempts to describe the on-going "history war" in modern Singapore history, between the dominant narrative promoted by the state and the alternative accounts. The master narrative is increasingly being challenged by the latter.